Proceedings of the 18th International Electronic Conference on Synthetic Organic Chemistry 2014
DOI: 10.3390/ecsoc-18-a044
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Investigation of TiO2-Graphene Nanocomposites

Abstract: In this study TiO2 was photosensitized by graphene to improving the visible spectral absorption and photoactivity under visible light irradiation. TiO2 was added to different content of graphene oxide and with hydrothermal method and 1, 3 and 5 percentage of graphene-TiO2 composite (TG) was synthesized. The prepared samples were characterized by XRD, Raman, DRS, and SEM.Photoelectrochemical experiments exhibited that the photocurrent response of three percentages of TG nanocomposite was higher than others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…Ti-O vibration is identified at 670 cm −1 . The left shoulder absorption band at 807 cm −1 and the minor peaks around 2800-3100 cm −1 are consistent with Ti-O-C binding, showing the chemisorption between TS and GD solutions [15,28]. The same peaks (2800-3100 cm −1 ) may be attributed to metal (in this case, Ti) and methyl groups (Ti-CH x ), as well [29].…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…Ti-O vibration is identified at 670 cm −1 . The left shoulder absorption band at 807 cm −1 and the minor peaks around 2800-3100 cm −1 are consistent with Ti-O-C binding, showing the chemisorption between TS and GD solutions [15,28]. The same peaks (2800-3100 cm −1 ) may be attributed to metal (in this case, Ti) and methyl groups (Ti-CH x ), as well [29].…”
Section: Resultssupporting
confidence: 62%
“…The other peak at 45.4 • is due to 211 anatase plane and appears when the film is deposited from the solution with TS:GD of 1:4 and annealed at 150 • C [18]. The reflection peak at 56.6 • is assigned to 211 anatase and 105 rutile planes [3,13,15]. These signals are weak in the composite films with low TiO 2 content, but are quite strong in the TiO 2 -rich film annealed at 150 • C. Another signature of TiO 2 , 200 anatase plane at 48 • only appears in the rich-TiO 2 film annealed at 150 • C. Therefore, a TiO 2 -rich composite film annealed at 150 • C shows ideal transformation of titanium precursors to crystalline TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The common procedure for ex-situ hybridization is to mix GO and modified TiO 2 with physical process such as ultrasound sonication and heat treatments. Rahmatollah et al [62] reported a facile one-step solvothermal method to synthesize the TiO 2 -graphene composite sheets by dissolving different mass ratios of GO and TiO 2 nanoparticles in anhydrous ethanol solution.…”
Section: Introductionmentioning
confidence: 99%